2008
DOI: 10.1002/jcp.21495
|View full text |Cite
|
Sign up to set email alerts
|

iNOS expression requires NADPH oxidase‐dependent redox signaling in microvascular endothelial cells

Abstract: Redox regulation of inducible nitric oxide synthase (iNOS) expression was investigated in lipopolysaccharide and interferon-γ (LPS+IFNγ)-stimulated microvascular endothelial cells from mouse skeletal muscles. Unstimulated endothelial cells produced reactive oxygen species (ROS) sensitive to inhibition of NADPH oxidase (apocynin and DPI), mitochondrial respiration (rotenone) and NOS (L-NAME). LPS+IFNγ caused a marked increase in ROS production; this increase was abolished by inhibition of NADPH oxidase (apocyni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 43 publications
4
100
1
1
Order By: Relevance
“…Peng et al (43) showed that LPSmediated TNF-␣ expression in cardiomyocytes was dependent on gp91phox and p38 kinase activation. Similarly, Wu et al (46) and Patel et al (45) showed Nox2 and Nox4 mediated LPS-dependent MAPK activation in aortic smooth muscle cells and skeletal muscle microvascular endothelial cells, respectively. Our data regarding HPMECs are consistent with the studies mentioned above and support the regulation of proinflammatory MAPK activation by Nox isoforms.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 77%
“…Peng et al (43) showed that LPSmediated TNF-␣ expression in cardiomyocytes was dependent on gp91phox and p38 kinase activation. Similarly, Wu et al (46) and Patel et al (45) showed Nox2 and Nox4 mediated LPS-dependent MAPK activation in aortic smooth muscle cells and skeletal muscle microvascular endothelial cells, respectively. Our data regarding HPMECs are consistent with the studies mentioned above and support the regulation of proinflammatory MAPK activation by Nox isoforms.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 77%
“…Part of the evidence for this mechanism is that injection of ascorbate (200 mg/kg) prevents CLP from elevating the concentration of NO metabolites in plasma (64). Further, ascorbate injection blocks the increase by CLP of iNOS mRNA expression in microvascular endothelial cells at 3 h after CLP, apparently due to inhibition by ascorbate of NADPH oxidase activity (63,65). Parenteral ascorbate also blocks the increases in total NOS, iNOS, and neuronal NOS (nNOS) activities in skeletal muscle of CLP mice (68) (Fig.…”
Section: Ascorbate Preserves Arteriolar Reactivitymentioning
confidence: 99%
“…Tyrosine residues in the catalytic subunit of PP2A (PP2Ac) become nitrated in microvascular endothelial cells exposed to LPS + IFNc, because this insult increases NADPH oxidase synthesis of superoxide, iNOS synthesis of NO, and consequently the production of peroxynitrite from superoxide and NO (62,65). The tyrosine nitration of PP2Ac increases the phosphatase activity of PP2A, which dephosphorylates serine and threonine residues in occludin (24,41).…”
Section: Extravasation Of Plasma Proteins and Fluidmentioning
confidence: 99%
See 2 more Smart Citations